At-sea distribution of marine predators around South Georgia during austral winter, with implications for fisheries management - Kate A. Owen; Meghan Goggins; Andy Black; Jonathan Ashburner; Alastair Wilson; Philip R. Hollyman; Philip N. Trathan; Claire M. Waluda; Martin A. Collins (Polar Biology, 2024)
The sub-Antarctic island of South Georgia is surrounded by highly productive waters, supporting dense aggregations of Antarctic krill ( Euphausia superba ), a vital food source for globally important seabird and marine mammal populations. These waters also support a commercial fishery for Antarctic krill. Regular monitoring of key krill predator species is undertaken at South Georgia to detect any changes in the ecosystem in response to harvesting activities. This monitoring provides essential data but is focused on land-breeding animals during the austral summer, whilst the krill fishery operates exclusively in winter. Here, we report the results of at-sea surveys to investigate abundance and distribution of krill-dependent predators from winter 2010 and 2011, which represented a “poor” krill year and “good” krill year, respectively. Correspondingly in 2011 higher numbers of krill predators were observed; notably Antarctic fur seals ( Arctocephalus gazella ) across the northern shelf. Spatial overlap between fur seals and the krill fishery occurred mainly within the krill fishery hotspot to the north-east, highlighting the potential for locally high levels of competition. Cetaceans were observed during both survey years, but in low numbers compared to recent studies. Gentoo penguins ( Pygoscelis papua ) were the most frequently observed penguin species, showing an inshore distribution and almost no overlap with the krill fishery. Diving-petrels ( Pelecanoides spp.) were the most abundant flying seabirds, observed across all transects, with particularly high densities to the south in early winter 2010. In conclusion, this survey provides valuable baseline data on the distribution of South Georgia’s predators during the winter months.